Review shows that using surfactant a number of times or as a vehicle for budesonide may reduce the risk of bronchopulmonary dysplasia. (22nd December 2017) - Hascoët, JM; Picaud, JC; Ligi, I; Blanc, T; Daoud, P; Zupan, V; Moreau, F; Guilhoto, I; Rouabah, M; Alexandre, C; Saliba, E; Storme, L; et al.
Abstract: Aim: Bronchopulmonary dysplasia (BPD) remains the most common respiratory morbidity in immature infants. This review describes the diagnosis of BPD has evolved and summarises the therapeutic approaches that have made it possible to limit the incidence of BPD. Method: We reviewed the literature from the first definition of BPD by Northway in 1967 to the surfactant treatment policies that are currently in use, drawing on more than 50 papers up to 2017. Results: Our review showed that improvements in neonatal survival have been associated with an increased risk of severe BPD, significant levels of long‐term morbidity and the increased use of healthcare resources. These issues have encouraged researchers to explore potential new treatments that limit the incidence of BPD. Repeated surfactant instillation and the use of surfactant as a vehicle for budesonide are promising strategies for alleviating the burden of chronic lung disease. Ongoing research on surfactant or stem cell therapy may further improve the respiratory prognosis for prematurely born children. Conclusion: Considerable research has been carried out into the increase in BPD, which has resulted from improvements in neonatal survival. Key areas of research include repeated surfactant administration, using surfactant as a vehicle for budesonide and stem cell therapy. Abstract :